Ultrafast spin-flip exciton conversion and narrowband sky-blue luminescence in a fused polycyclic selenaborin emitter - Sudhir K. Keshri; Guanting Liu; Takuma Yasuda; Takuma Yasuda (Frontiers in Chemistry, 2024)
Thermally activated delayed fluorescence (TADF) materials with high photoluminescence quantum yields and fast reverse intersystem crossing (RISC) capabilities are highly desirable for applications in high-efficiency organic light-emitting diodes. Herein, we report the synthesis as well as structural and photophysical properties of 5,9-diselena-13b-boranaphtho[3,2,1-de]anthracene (SeBSe) as a narrowband-emissive TADF material. The incorporation of two selenium atoms into the boron-fused pentacyclic π-core results in a small singlet–triplet energy gap (ΔEST) and thereby significant TADF properties. Moreover, theoretical calculations revealed a noticeable spin-orbit coupling enhancement between the singlet and triplet manifolds in SeBSe by virtue of the heavy-atom effect of selenium atoms. Consequently, SeBSe allows ultrafast spin-flip RISC with the rate constant surpassing 108 s−1, which far exceeds the corresponding fluorescence radiative decay rate (∼106 s−1), enabling an ideal singlet–triplet superimposed excited state.